Asuhan Keperawatan Pasien dengan Nyeri Akut pada Hipertensi di RSAU dr. Esnawan Antariksa Jakarta Timur - Edo Fidelis Martin; Revie Fitria Nasution (Jurnal Persada Husada Indonesia, 2020)
Nursing care for clients with hypertension is a series of nursing processes in overcoming problems with clients. Hypertension is systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg. Nursing care is carried out to prevent and reduce mortality in the future. The purpose of this study was to obtain an overview of the implementation of nursing care for clients who experience acute pain with hypertension at RSAU dr. Esnawan Antariksa, East Jakarta. This research design uses descriptive qualitative research with a case study and intervention approach. Participants in this study were 2 (two) clients and their families with acute pain nursing problems and medical diagnoses of hypertension. The characteristics of the participants were the same sex, age 45–64 years, blood pressure >140/90mmHg, pain complaints on a moderate scale (4-6) and a severe scale (7-9). After nursing action on client 1, 3 nursing diagnoses were obtained with the criteria for the problem resolved, namely: acute pain associated with increased cerebral vascular pressure, activity intolerance related to general weakness, and knowledge deficit related to hypertension related to lack of information obtained. While on client 2, there were 3 nursing diagnoses with the criteria for resolved problems, namely: acute pain associated with increased cerebral vascular pressure, weight was more related to adequate nutritional intake, and knowledge deficits about hypertension related to lack of information obtained. The results of giving breath relaxation actions can reduce pain levels in clients with hypertension.